2013
DOI: 10.1177/1541204013478973
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Externalizing Behavior Among Youth in the United States

Abstract: Despite research demonstrating that approximately 5% of study populations are composed of severely antisocial persons who account for a disproportionate share of problem behaviors, there have been no nationally representative studies assessing this phenomenon among adolescents. Using a large nationally representative sample (N ¼ 18,614), we identified a severe group (4.7% of respondents) characterized by involvement in varied and intensive externalizing behaviors, greater internalizing, lower academic achievem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
127
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 203 publications
(142 citation statements)
references
References 64 publications
12
127
1
2
Order By: Relevance
“…These findings corroborate other correlates found in previous studies (Muula, Rudatsikira, & Siziya, 2008;Vaughn, DeLisi, Salas-Wright, & Maynard, 2014;Vaughn, Perron, Abdon, Olate, & Wu, 2012;Wilkinson & Fagan, 2001;Wintemute, 2015). However, within this externalizing behavior spectrum we found some evidence of differential correlates by race/ethnicity.…”
Section: Discussionsupporting
confidence: 92%
“…These findings corroborate other correlates found in previous studies (Muula, Rudatsikira, & Siziya, 2008;Vaughn, DeLisi, Salas-Wright, & Maynard, 2014;Vaughn, Perron, Abdon, Olate, & Wu, 2012;Wilkinson & Fagan, 2001;Wintemute, 2015). However, within this externalizing behavior spectrum we found some evidence of differential correlates by race/ethnicity.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that our study found the rate of university students carrying knives, penknives, guns and similar sharp and piercing weapons (13.7%) to be higher than in other studies in the university population of Turkey (7.9%-11.1%), shows that such behavior is on the rise among students (54,55). Our finding that the rate of injuries sustained as a result of carrying a piercing or sharp weapon and involvement in a fight is higher among men in comparison to women (40,54,56,57) may be explained by social gender roles imposed on men, expecting them to be brave, strong, and to become warriors.…”
Section: The Prevalence Of Risky Behaviormentioning
confidence: 71%
“…Our study demonstrates that there is a higher risk of substance use among those who engage in physical fights and carry piercing or sharp weapons. In studies completed in the United States, results were found to demonstrate a strong relationship between carrying a gun on campus and substance use, as well as substance sales and substance-related crimes (40,57). An early start of violence and crime may indicate a risk of substance use in later years.…”
Section: Relationship Between Risky Behavior and Substance Usementioning
confidence: 99%
“…Given the exploratory nature of the present study, further studies are needed to determine the links between gambling and criminality in homeless youth. In fact, it would be interesting to compare the profile of this at-risk group to that of the adolescents presenting the most severe externalizing behaviors [66].…”
Section: Discussionmentioning
confidence: 99%